PENGARUH PENGETAHUAN, KESUKAAN DAN KEYAKINAN KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN MOBIL HONDA PADA KONSUMEN DI KOTA MAKASSAR - Muh. Indra Fauzi Ilyas (Jurnal Bisnis dan Kewirausahaan, 2017)
This study aims to: a) analyze the influence of knowledge on the decision of purchasing Honda cars to the consumers in Makassar City; b) analyze the influence of likes to the decision of Honda car purchase in Makassar City; c) analyze the influence of consumer confidence in the decision of purchasing Honda cars to consumers Makassar city. The analysis method used is descriptive analysis method and multiple linear regression analysis. The results showed that: From the calculation results of Full Model Regression analysis with the help of SPSS program obtained F counted 12,414 with a probability level of 0.000 (significant). While F table equal to 4.9646 thus F count is bigger than F table (12.414> 4.9646) and also probability is much smaller than 0.05, it means that knowledge, likeness and consumer belief simultaneously influence to purchasing decision of Honda car to consumer in Makassar City. With the influence of these three variables explained that before making a car purchase decision, consumers consider the brand image of the products offered based on the knowledge, likes and beliefs that the whole variable is significant, meaning t arithmetic> t table, and found the dominant confidence variable (X3) is based on Regression coefficient of B value of 0.375. This means that the second hypothesis is accepted, which indicates in the purchase decision making, the belief of the consumer is very decisive as it is the consumer's trust over the product offered.